The Histone Marks Signature in Exonic and Intronic Regions Is Relevant in Early Response of Tomato Genes to Botrytis cinerea and in miRNA Regulation - Crespo-Salvador, Óscar (Plants (Basel), 2020)
Research into the relationship between epigenetic regulation and resistance to biotic stresses provides alternatives for plant protection and crop improvement. To unravel the mechanisms underlying tomato responses to Botrytis cinerea, we performed a chromatin immunoprecipitation (ChIP) analysis showing the increase in H3K9ac mark along the early induced genes SlyDES, SlyDOX1, and SlyLoxD encoding oxylipin-pathway enzymes, and SlyWRKY75 coding for a transcriptional regulator of hormonal signaling. This histone mark showed a more distinct distribution than the previously studied H3K4me3. The RNAPol-ChIP analysis reflected the actual gene transcription associated with increased histone modifications. A different pattern of marks in the oxylipin-related genes against P. syringae supported a pathogen-specific profile, while no significant differences occurred in SlyWRKY75. The epigenetic regulation of SlyWRKY75 by the intron-binding miR1127-3p was supported by the presence of SlyWRKY75 pre-mRNA in control plants. Interestingly, mRNA was found to be accumulated in response to B. cinerea and P. syringae, while reduction in miRNA only occurred against B. cinerea. The intronic region presented a similar pattern of marks than the rest of the gene in both pathosystems, except for H3K4me3 in the miRNA binding site upon B. cinerea. We located the gene encoding Sly-miR1127-3p, which presented reduced H3K4me3 on its promoter against B. cinerea.